Negative pressure therapy as palliative treatment for a colonic fistula. Issue 2 (29th August 2012) - Ruiz‐Lopez, Manuel; Titos, Alberto; Gonzalez‐Poveda, Ivan; Carrasco, Joaquin; Toval, Jose Antonio; Mera, Santiago; Santoyo, Julio
<x xml:space="preserve">Abstract</x> Colonic fistulas in an open wound are always a challenge for colorectal surgeons, and this report provides a technique for the appropriate management of these cases. We communicate the use of a negative pressure dressing therapy as part of the palliative care for a patient following the development of an enterocutaneous fistula. The use of this therapy allowed us to keep the patient clean and comfortable during the last few days of his life.